2013
DOI: 10.1016/j.burns.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of operative burns at Kijabe Hospital from 2006 to 2010: Pilot study of a web-based tool for creation of the Kenya Burn Repository

Abstract: Introduction In order to implement effective burn prevention strategies, the WHO has called for improved data collection to better characterize burn injuries in low and middle income countries (LMIC). This study was designed to gather information on burn injury in Kenya and to test a model for such data collection. Methods The study was designed as a retrospective case series study utilizing an electronic data collection tool to assess the scope of burn injuries requiring operation at Kijabe Hospital from Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
3
16
0
Order By: Relevance
“…This finding matches data from developing countries and differs from data in developed countries, where the largest age group is children aged 2-5 years [3,11]. Males accounted for 72% of patients, which corresponds with most reported studies [9,12,13], although some controversial findings have been published elsewhere [11,14,15]. Overall, 15% of cases of all burns were suicide-related and in 75% of cases women set themselves on fire.…”
Section: Risk Factorssupporting
confidence: 82%
“…This finding matches data from developing countries and differs from data in developed countries, where the largest age group is children aged 2-5 years [3,11]. Males accounted for 72% of patients, which corresponds with most reported studies [9,12,13], although some controversial findings have been published elsewhere [11,14,15]. Overall, 15% of cases of all burns were suicide-related and in 75% of cases women set themselves on fire.…”
Section: Risk Factorssupporting
confidence: 82%
“…The higher risk among adult men that has been observed in previous studies from the area regarding severe and fatal burns [8][9][10][11][12]20] was in this setting found in fire burns in younger adult men and in hot liquid burns in older men. The reasons for these gender differences are likely to be multifaceted and connected to different exposures where environment and behaviour interact, falling hardest on men in this resource-constrained setting.…”
Section: Main Findingsmentioning
confidence: 62%
“…There are no reported gender differences in burn mechanism [10,16,18,26] and studies examining gender differences in other injury aetiology or care parameters are scarce in SSA. Studies of specific causes have reported gender differences with women overrepresented among burns due to kerosene stove explosions [27] and men among petrol fire disaster victims [28].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…[9][10][11] The most observed type of burn is second-degree burn and in order to treat, various types of medicines are available. Aloe vera can also be used for healing burns.…”
Section: Discussionmentioning
confidence: 99%